On "Thomistic Kabbalah" - Milbank, John (Modern theology, 2011)
The Christian Bible was from the outset a dogmatic and Christological conception, which entailed a mystical reading of signs and events, a practise of speculation at once narratological and phenomenological. The trilogy of Olivier-Thomas Venard OP - Thomas d'Aquin, poète théologien - is proposed as crucial to understanding how Thomas Aquinas preserves the authentic biblical character of Christian theology, proceeding along the diagonal axis of the mystagogical, an axis neither purely vertical nor purely horizontal but a blending of both at once. Here a reading of Aquinas is offered as initiating a participational ‘linguistic turn’, an alternative modernity that can heal the dissociation of the science of being from the phenomenal and hermeneutical embeddings in which human life is constituted.